Branched 1, 2, 3‐Triazolium‐Functionalized Polyacetylene with Enhanced Conductivity. Issue 24 (15th November 2016) - Wu, Jianhua; Wang, Cuifang; Zhou, Dandan; Liao, Xiaojuan; Xie, Meiran; Sun, Ruyi
Abstract : Metathesis cyclopolymerization of mono‐ or bissubstituted 1, 6‐heptadiynes is undergone to generate the ionic polyacetylenes (iPAs) with branched 1, 2, 3‐ttriazolium pendants, which possess relatively high intrinsic ionic conductivities of 1.4 × 10 −5 –2.1 × 10 −5 S cm −1 at 30 °C. The doping treatment with lithium bis(trifluoromethanesulfonyl)imide endows iPAs with enhanced ionic conductivities of 2.5 × 10 −5 –4.3 × 10 −5 S cm −1 . Further doping with iodine, iPAs show ionic and electronic dual conductivities of 4.5 × 10 −5 –7.1 × 10 −4 and 1.5 × 10 −6 –4.5 × 10 −6 S cm −1, respectively. Therefore, the doped iPAs demonstrate the potential in the area of conducting polymers and polymeric electronics. Abstract : Metathesis cyclopolymerization of ionic 1, 6‐heptadiynes generates polyacetylenes bearing branched 1, 2, 3‐triazolium pendants, which display the simultaneous ionic and electronic conductivities of 7.1 × 10 −4 and 4.5 × 10 −6 S cm −1 at 30 °C, respectively, when doped with LiTFSI and iodine.